Specification, authoring and prototyping of personalised workplace learning solutions. (18th October 2007) - Dolog, Peter; Kravcik, Milos; Cristea, Alexandra; Burgos, Daniel; Bra, Paul; Ceri, Stefano; Devedzic, Vladan; Houben, Geert-Jan; Libbrecht, Paul; Matera, Maristella; Melis, Erica; Nejdl, Wolfgang; et al.
The main goal of this document is to survey the existing approaches for the authoring and engineering of personalisation and adaptation in e-learning systems. This document enables the comparison of various methods and techniques, and facilitates their integration or reuse. It offers a cohesive reference for people dealing with areas which rely on adaptive solutions.